Determinants of Intention to Purchase Photovoltaic Panel System: An Integration of Technology Acceptance Model and Theory of Planned Behaviour - Fatoki, Olawale (International Journal of Energy Economics and Policy, 2022)
The emission of carbon dioxide and other greenhouse gases through electricity consumption by firms is one the significant drivers of climate change. Renewable energy can help to minimise the ecological footprint associated with the production and consumption of fossil fuels. Drawing on the Technology Acceptance model (TAM) and an extended Theory of Planned Behaviour (TPB), the study examined the determinants of intention to purchase rooftop photovoltaic (PV) panel system in residences in South Africa.. The quantitative research design was adopted for the study and the cross-sectional survey method was used for data collection. The hypotheses of the study were tested using the Partial Least Square Structural Equation modelling (PLS SEM). The results of the empirical study indicated that environmental concern, green perceived usefulness, perceive ease of use are associated with attitude and intention to purchase rooftop photovoltaic (PV) panel system. In addition, attitude, perceived behavioural control and awareness are positively related to intention to purchase rooftop photovoltaic (PV) panel system. Theoretically, the study confirms the applicability of an integrated model that consists of the TAM and TPB in explaining the intention to install rooftop photovoltaic (PV) panel system. Recommendations to improve the adoption of rooftop photovoltaic (PV) panel system in residences are suggested.